2017
DOI: 10.1186/s13030-017-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of outpatients with somatization symptoms treated at a Japanese psychosomatic medicine clinic

Abstract: BackgroundSomatization is produced due to the summation of psychological factors, irrespective of the presence or absence of physical factors. A group of diseases with severe pain and other disorders exhibit so-called Medically Unexplained Symptoms (MUS), and the characteristics of patients with MUS are largely unexplained. In this paper, the characteristics of a series of new patients with somatization treated in a Japanese university hospital are discussed.MethodThe subjects were 871 patients who newly visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In a study carried out by Dönmez et al in Antalya, Turkey female gender has been found to increase the risk of somatization disorder by 1.9 times (17). In a study conducted with SCL90-R questionnaire in Germany and in another study carried out in Japan examining the clinical characteristics of patients with somatization Konuralp Tıp Dergisi 2020;12(2): 183-190 188 symptoms, somatization disorder was found to be more prevalent in women ( 18) (19). In the study by Kaya et al on the epidemiology of Somatoform Disorders, it was emphasized that the maledominated structure of the society and the more passive use of the body language of the women who remain in a passive position from childhood can cause somatization disorders to be seen more frequently in women (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Dönmez et al in Antalya, Turkey female gender has been found to increase the risk of somatization disorder by 1.9 times (17). In a study conducted with SCL90-R questionnaire in Germany and in another study carried out in Japan examining the clinical characteristics of patients with somatization Konuralp Tıp Dergisi 2020;12(2): 183-190 188 symptoms, somatization disorder was found to be more prevalent in women ( 18) (19). In the study by Kaya et al on the epidemiology of Somatoform Disorders, it was emphasized that the maledominated structure of the society and the more passive use of the body language of the women who remain in a passive position from childhood can cause somatization disorders to be seen more frequently in women (20).…”
Section: Discussionmentioning
confidence: 99%
“…MUS is defined as “physical symptoms for which no clear or consistent organic pathology can be demonstrated” [ 1 ]. Our patients were diagnosed by physicians specializing in psychosomatic medicine, as described previously [ 2 ]. Patients with unknown BZD use history (eg, those prescribed at another hospital) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Cases of refractory MUS sometimes become persistent or chronic; therefore, it has been proposed that the treatment of MUS should be interdisciplinary because it has a complex clinical spectrum [ 1 ]. In our previous study, we reported various clinical symptoms of MUS [ 2 ] that complicate its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Given that illness behavior depends on the healthcare system and culture of a country, 1 it is necessary to investigate the behavior in each healthcare system. In systems wherein patients must first visit family physicians for referrals, MUS accounts for 5%–30% of primary care patient diagnoses 2 and 37%–68% of specialty care patient diagnoses 14,15 . On the contrary, Japan has a “free access” system wherein patients can utilize whatever kinds of outpatient services they like without referrals.…”
Section: Introductionmentioning
confidence: 99%